The New Bible Dictionary - Douglas, J. D.; Douglas, J. D. (James Dixon); Tyndale Fellowship for Biblical Research (Grand Rapids, Michigan : Eerdmans, 1962)
Encyclopedia of Bible lore, based on recent advances in archaeology, issued under auspices of Tyndale Fellowship for Biblical Research
Includes bibliographies and indexes
Keywords: Bible -- Dictionaries; Bible Dictionary; Dictionaries; Dictionaries